Musical Methods in Teaching Arabic to Preschool Children: A Pedagogical Perspective - Alhadi, Ahmed; Muhammad Dani Fauzan Sajid (International Journal of Pedagogy, 2025)
Arabic is one of the international languages spoken in various countries, and introducing it during early childhood can facilitate more effective language acquisition. Young children possess remarkable cognitive abilities, allowing them to absorb new information rapidly. In language education, teaching methods are one of several crucial factors influencing learning outcomes, alongside learning objectives, student characteristics, and teacher personality. This study explores the use of singing as a pedagogical method in teaching Arabic to early childhood learners. Employing a literature review approach, the research analyzes existing studies and theoretical perspectives to highlight the potential of singing as an engaging and effective instructional strategy. Findings suggest that Arabic language instruction for young children can be significantly enhanced through appropriate teaching methods, with singing being a particularly promising approach due to its rhythmic, mnemonic, and motivational qualities. Other methods commonly used include reading (muthala'ah), memorization, and translation. This study contributes to the growing discourse on innovative language teaching practices in early childhood education.